Hubungan Antara Grit dengan Hope pada Siswa SMK Negeri 6 Surakarta - Mulia, Florine; Priyatama, Aditya Nanda (MANASA, 2025)
This quantitative study aims to examine the relationship between grit and hope among students at State Vocational School 6 Surakarta. Sampling was conducted using a purposive sampling method, involving 232 eleventh-grade students as participants. The dependent variable, hope, was measured using an adaptation of the Adult Hope Scale, while the independent variable, grit, was measured using the Short Grit Scale (Grit-S). Hypothesis testing was performed using the Pearson product-moment correlation method. The results showed a significant correlation, indicating a positive relationship between grit and hope. This suggests that higher levels of grit are associated with higher levels of hope among students, and vice versa. However, the strength of this relationship is classified as moderate. Additional analysis revealed a significant difference in the average hope scores between students in the accounting major and those in the Film Production major. While this study contributes to the growing body of literature on hope and grit among vocational high school students, several research limitations need to be taken into consideration.